Etiology and Management of Hemorrhagic Complications of Portal Hypertension in Children - Alejandro Costaguta; Fernando Alvarez (International Journal of Hepatology)
Portal hypertension in children represents a particular diagnostic and management challenge for several reasons: (1) treatment outcomes should be evaluated in relationship with a long-life expectancy, (2) pediatric patients with portal hypertension constitute an heterogeneous population, both in terms of individual characteristics and diversity of liver diseases; making comparison between treatment outcomes very difficult, (3) application of techniques and procedures developed in adult patients (v.gr. TIPS) face size limitations in small children, and (4) absence of data from well-controlled trials in children forces pediatric specialists to adapt results obtained from adult cohorts suffering from diseases such as HCV and alcoholic cirrhosis. Despite those limitations, substantial progress in the treatment of children with portal hypertension has been achieved in recent years, with better outcomes and survival. Two main factors influence our therapeutic decision: age of the patient and etiology of the liver disease. Therefore, diagnosis and treatment of complications of portal hypertension in children need to be described taking such factors into consideration. This paper summarizes current knowledge and expert opinion.